PATTERN OF CHEMOTHERAPY INDUCED TOXICITIES IN CHILDREN WITH EWING SARCOMA: A CASE SERIES - Manzoor, Rabiha; Naz, Shaista; Ali, Sobia; Tariq, Rabia; Shamraiz, Ifnan; Siddique, Abdul Wahab (Journal of Ayub Medical College Abbottabad, 2024)
Background: Ewing sarcoma is a rare and aggressive bone or soft tissue cancer that primarily affects children and adolescents. Estimated incidence of Ewing sarcoma is reported to be 1.2-2.9 in one million individuals in England and 1 in one million in the US. Objective was to determine the pattern, and influence of gender and age on chemotherapy-induced toxicities in children with Ewing sarcoma. It was a descriptive case series conducted at the Department of Pediatric Oncology, CMH Rawalpindi, from January 2014 to June 2023. Methods: Children of either gender aged less than 18 years and diagnosed cases of Ewing Sarcoma were enrolled. All patients were given VIDE (vincristine, ifosamide, doxorubicin, etoposide) chemotherapy and patients were observed for chemotherapy induced toxicities. Chi square test was used to analyze significance of age and gender on toxicity. Results: In a total of 59 children 35 (59.3%) were male and 24 (40.7%) female. Out of these 11 children expired. The mean age was 7.59±3.87 years. Younger age was strongly associated with higher occurrence of toxicity specifically children under 5 years being most affected (p<0.05). Neutropenia, nausea and vomiting, thrombocytopenia, and diarrhea were the most frequent adverse events observed in 53 (89.9%), 37 (62.7%), 36 (61.0%), and 36 (61.0%) patients respectively. There was no association of gender with chemotherapy induced toxicity. Neutropenic sepsis and diarrhea were positively associated with mortality in the 11 children who expired (p<0.05). Conclusion: Neutropenia, nausea and vomiting, mucositis, thrombocytopenia and diarrhea were the most frequent chemotherapy induced toxicities in children with Ewing sarcoma. Younger children specifically under 5 years have a higher chance of chemotherapy induced toxicities however gender did not seem to influence related toxicities. Neutropenic sepsis was the major predictor of mortality warranting higher vigilance and aggressive management of infections.